Demonstration of blood flow by color doppler in the femoral artery distal to arterial cannula during peripheral venoarterial-extracorporeal membrane oxygenation - K G Suresh Rao; T Muralikrishna; K R Balakrishnan (Annals of Cardiac Anaesthesia, 2017)
In spite of distal perfusion of the limb using a cannula, the limb can have ischemic events if there is an undetected kink or clot anywhere in the line or thrombus in the artery. There are several ways to monitor and assess the limb ischemia. Monitoring for clinical signs of limb ischemia like temperature change and pallor is reliable and mandatory. We report a method where we used color Doppler to document the blood flow. Curvilinear vascular probe of an echo machine is used to identify the flow in the distal femoral artery of the lower limb. . As we have demonstrated in the video attached, once flow to the distal limb perfusion system is shut off by closing the three way stop cock, we can appreciate the immediate cessation of flow in the artery by Doppler.